2022
DOI: 10.1101/2022.07.26.501544
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Connectome spectrum electromagnetic tomography: a method to reconstruct electrical brain source-networks at high-spatial resolution

Abstract: The discovery that the structural connectome serves as a compact representation of brain activity allowed us to apply compressed sensing to M/EEG source reconstruction of brain electrical activity. We show that the introduction of this biological constraint significantly increases the signal-to-noise ratio and spatial conspicuity of the reconstruction in human datasets. This significant gain in precision and accuracy could allow neuroscientists to extend their research beyond current limits.

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 84 publications
0
1
0
Order By: Relevance
“…For EEG data, a number of studies have shown promising results, namely, for dimensionality reduction (Tanaka et al, 2016; Kalantar et al, 2017), signal denoising (Cattai et al, 2021), and motor imagery (MI) decoding (Georgiadis et al, 2021; Cattai et al, 2022). Moreover, diffusion MRI-derived connectome harmonics have been used to characterize EEG data within a GSP setting, for tracking fast spatio-temporal cortical dynamics (Glomb et al, 2020b), their sparse representation (Rué-Queralt et al, 2021), and for source reconstruction (Rué-Queralt et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…For EEG data, a number of studies have shown promising results, namely, for dimensionality reduction (Tanaka et al, 2016; Kalantar et al, 2017), signal denoising (Cattai et al, 2021), and motor imagery (MI) decoding (Georgiadis et al, 2021; Cattai et al, 2022). Moreover, diffusion MRI-derived connectome harmonics have been used to characterize EEG data within a GSP setting, for tracking fast spatio-temporal cortical dynamics (Glomb et al, 2020b), their sparse representation (Rué-Queralt et al, 2021), and for source reconstruction (Rué-Queralt et al, 2022).…”
Section: Introductionmentioning
confidence: 99%